(untitled) (Physical Education, Health and Social Sciences, 2026)
This research aimed to establish the association between anthropometric characteristics and physical fitness levels among school children. The research methodology was based on a quantitative approach. A cross-sectional research design was employed for this study. The study population consisted of male school-children aged 9-11 years from five private and five government schools in Sargodha, Pakistan. A sample of n-304 children was selected using a convenience sampling method. Data normality was assessed using the Shapiro-Wilk test, and relationships between variables were analyzed using Pearson correlation analysis. Physical fitness variables, such as speed, balance, flexibility, muscular strength, push-ups, sit-ups, aerobic endurance, and handgrip strength, were measured against height, body weight, and body mass index (BMI) at a significance level of 0.05. The results established that height was task-specific to physical fitness, whereas body weight and BMI had significant negative correlations with balance, muscular strength, muscular endurance, and aerobic endurance, especially in children in private school settings. By comparison, positive relationships between handgrip strength and all anthropometric variables were observed in both school sectors. Overall, the findings showed that excessive body mass negatively influenced various components of physical fitness in schoolchildren, and it was suggested that regular school-based physical activity programs must be intensified to enhance overall fitness.